Structure–Activity Relationship Study of a Potent α‐Thrombin Binding Aptamer Incorporating Hexitol Nucleotides. Issue 43 (9th July 2020) - De Fenza, Maria; Eremeeva, Elena; Troisi, Romualdo; Yang, Hui; Esposito, Anna; Sica, Filomena; Herdewijn, Piet; D'Alonzo, Daniele; Guaragna, Annalisa
Abstract: The replacement of one or more nucleotide residues in the potent α‐thrombin‐binding aptamer NU172 with hexitol‐based nucleotides has been devised to study the effect of these substitutions on the physicochemical and functional properties of the anticoagulant agent. The incorporation of single hexitol nucleotides at the T9 and G18 positions of NU172 substantially retained the physicochemical features of the parent oligonucleotide, as a result of the biomimetic properties of the hexitol backbone. Importantly, the NU172‐T H 9 mutant exhibited a higher binding affinity toward human α‐thrombin than the native aptamer and an improved stability even after 24 h in 90 % human serum, with a significant increase in the estimated half‐life. The anticoagulant activity of the modified oligonucleotide was also found to be slightly preferable to NU172. Overall, these results confirm the potential of hexitol nucleotides as biomimetic agents, while laying the foundations for the development of NU172‐inspired α‐thrombin‐binding aptamers. Abstract : Something NU : The first structure–activity relationship (SAR) study of the potent anticoagulant agent NU172, following the replacement of one or more nucleotides with their unnatural counterparts belonging to the HNA (hexitol nucleic acids) family, is herein reported. Compared with unmodified NU172, one HNA‐containing mutant exhibited preferable physicochemical and functional properties, because of the higher binding affinity to α‐thrombin, the improved stability in human serum, and the slightly enhanced anticoagulant activity.